Governança no esporte: a efetividade de iniciativas de combate à corrupção pela ótica de atletas e técnicos de atletismo - Brito, Fábio Dias (2015)
Ethical behavior are of great importance in the conduct of business between any business and are essential to the very interaction between individuals in society, in which they occur corrupt behavior, which can be so considered not legitimate from the ethical point of view and so we fought, including in sports. This study sought to articulate the constructs corruption and governance, to support research to adopt governance practices contributes in the fight against corruption in sport. Having as object the athletics, athletes and coaches were asked about how effective these measures would be, in your opinion, if adopted by the national body sport administration to which they are affiliated. In addition to this question at the operational level, it was also prepared a checklist, based on the survey of Marques and Costa (2009) and documentary analysis of the organization, which was confronted by the administrative direction of the organization, representing the strategic level of athletics. At the same time, it was also asked to athletes and coaches, their degree of permissiveness to corrupt actions as Lavena (2013) protocol. The study used the qualitative method at a stage in advance, exploratory and quantitative in the following, descriptive character. The collected data were treated by analysis of variance to find significance in the effectiveness of the actions and are described and presented in the results, which showed that between governance dimensions, only three of them (ownership, board of directors and independent audit) figured degree of statistical significance needed to be considered effective in combating certain corrupt actions in the sport, according to the procedure used, in the opinion of the athletes and coaches of athletics in the sample under the conditions tested in this study.